Komunikasi Antarpribadi untuk Membangun Kedekatan Antara Relawan Komunitas Sahabat Anak Kanker (SAK) Malang dengan Anak Penderita Kanker - Sholihah, Umi (Universitas Brawijaya, 2022)
Pediatric cancer patients often experience side effects from treatment, both physically and psychologically. The impact of this treatment, necessitates special assistance, which can be done through interpersonal communication to provide support for children with cancer. However, previous studies have not focused much on the closeness that ultimately builds on forms of interpersonal communication in the world of health. So, through phenomenological design, this study aims to determine interpersonal communication carried out to build closeness between volunteers of the Malang Cancer Child Friends Community (SAK) with children with cancer. Data collection was conducted by in-depth interviews with six informants who were SAK volunteers. The results of this study show that in general volunteers interpret the purpose of mentoring to build relationships, help, and comfort children with cancer. Meanwhile, in terms of the closeness of volunteers with children with cancer, volunteers interpret closeness based on the intensity of meetings, children's desire to meet volunteers, and volunteers' personal abilities in approaching children. Furthermore, in looking at the characteristics of communication, in general, volunteers recognize differences in terms of physical, psychic, and child maturity. So this condition requires volunteers to be more careful and patient in communicating with children with cancer.